EVALUATION OF THE EFFECT OF EXOGENOUS PUTRESCINE DURING THE MATURATION AND GERMINATION in vitro OF SOMATIC EMBRYOS IN TWO AGAVE GENOTYPES - Sandra Yarenssy Martínez-Martínez; Amaury Martín Arzate-Fernández; Monserrath Hernández-Solis; Laura Acosta-Villagran (Tropical and Subtropical Agroecosystems, 2023)
Background. Agaves are an important economic source in industrial products, in the food and pharmaceutical industry, steroidal animal feed, ornamental plants and as a material for biofuels. Despite their economic importance, some species present problems in their conventional propagation, which makes their reproduction difficult and has caused some species to be in some risk category. Therefore, there is a need to develop efficient protocols for in vitro micropropagation via somatic embryogenesis. The positive effect of the application of exogenous putrescine on the maturation and germination of somatic embryos is known. Objective. To determine the effect of exogenous putrescine on the maturation and germination of somatic embryos of A. cupreata and A. angustifolia. Methodology. Two concentrations of putrescine (100 and 150 mg/L) and two controls, one positive and one negative, were evaluated in the somatic embryo maturation medium and later in the germination of somatic embryos. Results. Putrescine favors the maturation and germination of somatic embryos in both species. Implications. The results of this research contribute to a better understanding of the process of somatic embryogenesis and open the possibility of applying putrescine in the process of somatic embryogenesis at a commercial level. Conclusion. Exogenous putrescine in culture medium significantly improves the maturation and germination of somatic embryos in Agave.